Olympia, Griechenland. Die Arbeiten der Jahre 2018 bis zum Frühjahr 2020 - Senff, Reinhard (e-Forschungsberichte des DAI, 2020)
During the time from 2018 until spring 2020 except for a sondage in the southwest corner of the courtyard in the Leonidaion (cf. report of Christa Schauer, Claudia Mächler, Stefan Distler) at Olympia no excavations were carried out. The excavations in the frame of the research project concerning the ancient Agora have preliminarily been suspended, as in 2016 and 2017 only Late Antique structures and two wells of the Classical Period had been found. The focus of the activities during the period of this report thus lay on the processing of finds, building research, the development of the excavation´s infrastructure and preparations for complex restoration-projects of several buildings at the Archaeological Site.